Mutations in centrosomin reveal requirements for centrosomal function during early Drosophila embryogenesis. - Vaizel-Ohayon, D.; Schejter, E.D. (Current Biology, 1999)
BACKGROUND:Although centrosomes serve as the primary organizing centers for the microtubule-based cytoskeleton in animal cells, various studies question the requirements for these organelles during the formation of microtubule arrays and execution of microtubule-dependent processes. Using a genetic approach to interfere with centrosomal function, we present an assessment of this issue, in the context of early embryogenesis of the fruit fly Drosophila melanogaster. RESULTS:We identified mutant alleles of the centrosomin (cnn) locus, which encodes a core component of centrosomes in Drosophila. The cnn mutant flies were viable but sterile. The normal course of early embryonic development was arrested in all progeny of cnn mutant females. Our analysis identified a failure to form functional centrosomes and spindle poles as the primary mutant phenotype of cnn embryos. Various aspects of early development that are dependent on cytoskeletal control were disrupted in cnn mutant embryos. In particular, structural rearrangements of cortical microfilaments were strongly dependent on proper centrosomal function. CONCLUSIONS:Centrosomin is an essential core component of early embryonic centrosomes in Drosophila. Microtubule-dependent events of early embryogenesis display differential requirements for centrosomal function.